2019
DOI: 10.1080/20013078.2019.1698795
|View full text |Cite
|
Sign up to set email alerts
|

MiR155‐5p in adventitial fibroblasts‐derived extracellular vesicles inhibits vascular smooth muscle cell proliferation via suppressing angiotensin‐converting enzyme expression

Abstract: 2020) MiR155-5p in adventitial fibroblastsderived extracellular vesicles inhibits vascular smooth muscle cell proliferation via suppressing ABSTRACT Proliferation of vascular smooth muscle cells (VSMCs) plays crucial roles in vascular remodelling and stiffening in hypertension. Vascular adventitial fibroblasts are a key regulator of vascular wall function and structure. This study is designed to investigate the roles of adventitial fibroblasts-derived extracellular vesicles (EVs) in VSMC proliferation and vasc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
69
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 98 publications
(72 citation statements)
references
References 51 publications
2
69
0
Order By: Relevance
“…MiR155-5p mimic inhibited ACE mRNA and protein expression in VSMCs of both WKY rats and SHR ( Figure 3A), confirming our previous findings that ACE is one of the targets of miR155-5p, and miR155-5p negatively regulates ACE expression in VSMCs in rat [17]. The miR155-5p inhibitor increased ACE expressions in VSMCs of both WKY rats and SHR ( Figure 3B), suggesting endogenous miR155-5p has a role in inhibiting ACE expression in WKY rats and SHR.…”
Section: Effects Of Mir155-5p Mimic and Inhibitor On Ace Expressionsupporting
confidence: 90%
See 4 more Smart Citations
“…MiR155-5p mimic inhibited ACE mRNA and protein expression in VSMCs of both WKY rats and SHR ( Figure 3A), confirming our previous findings that ACE is one of the targets of miR155-5p, and miR155-5p negatively regulates ACE expression in VSMCs in rat [17]. The miR155-5p inhibitor increased ACE expressions in VSMCs of both WKY rats and SHR ( Figure 3B), suggesting endogenous miR155-5p has a role in inhibiting ACE expression in WKY rats and SHR.…”
Section: Effects Of Mir155-5p Mimic and Inhibitor On Ace Expressionsupporting
confidence: 90%
“…VSMC migration contributes to maladaptive vascular remodeling in hypertension and is associated with the pathogenesis of hypertension and related organ damage [34][35][36]. Our previous study showed that extracellular vesicles derived from aortic adventitial fibroblasts of normal rats inhibited VSMC proliferation by delivering miR155-5p to VSMCs [17]. The primary new findings of the present study are that miR155-5p inhibits the migration of VSMC from SHR by suppressing ACE expression and its downstream production of superoxide anion and inflammatory factors in VSMCs of SHR.…”
Section: Discussionsupporting
confidence: 56%
See 3 more Smart Citations